Response of Dissolved Carbon and Nitrogen Concentrations to Moderate Nutrient Additions in a Tropical Montane Forest of South Ecuador - Velescu, Andre; Valarezo, Carlos; Wilcke, Wolfgang (Frontiers in Earth Science, 2016)
In the past two decades, the tropical montane rain forests in south Ecuador experienced increasing deposition of reactive nitrogen mainly originating from Amazonian forest fires, while Saharan dust inputs episodically increased deposition of base metals. Increasing air temperature and unevenly distributed rainfall have allowed for longer dry spells in a perhumid ecosystem. This might have favored mineralization of dissolved organic matter (DOM) by microorganisms and increased nutrient release from the organic layer. Environmental change is expected to impact the functioning of this ecosystem belonging to the biodiversity hotspots of the Earth. In 2007, we established a nutrient manipulation experiment (NUMEX) to understand the response of the ecosystem to moderately increased nutrient inputs. Since 2008, we have continuously applied 50 kg ha-1 a-1 of nitrogen (N), 10 kg ha-1 a-1 of phosphorus (P), 50 kg + 10 kg ha-1 a-1 of N and P and 10 kg ha-1 a-1 of calcium (Ca) in a randomized block design at 2000 m a.s.l. in a natural forest on the Amazonia-exposed slopes of the south Ecuadorian Andes. Nitrogen concentrations in throughfall increased following N+P additions, while separate N amendments only increased nitrate concentrations. Total organic carbon (TOC) and dissolved organic nitrogen (DON) concentrations showed high seasonal variations in litter leachate and decreased significantly in the P and N+P treatments, but not in the N treatment. Thus, P availability plays a key role in the mineralization of DOM. TOC/DON ratios were narrower in throughfall than in litter leachate but their temporal course did not respond to nutrient amendments. Our results revealed an initially fast, positive response of the C and N cycling to nutrient additions which declined with time. TOC and DON cycling only change if N and P supply are improved concurrently, while NO3-N leaching increases only if N is separately added. This indicates co-limitation of the microorganisms by N and P. The current increasing reactive N deposition will increase N export from the root zone, while it will only accelerate TOC and DON turnover if P availability is simultaneously increased. The Saharan dust-related Ca deposition has no impact on TOC and DON turnover.